2019
DOI: 10.14233/ajchem.2019.22045
|View full text |Cite
|
Sign up to set email alerts
|

Docking, Synthesis and Biological Evaluation of Novel Diketoquinoline Analogues as HIV-1 Integrase Inhibitor

Abstract: A series of novel diketoquinoline acid derivatives as potential anti-HIV-1 Integrase inhibitors were docked, synthesized and characterized by IR, NMR , CHN and MS spectral analysis. Many compounds were identified and docked in integrase pocket. The target diketoquinolines were prepared from substituted oxoquinoline-3-carboxylate. In vitro biological evaluation revealed that some of the titled compounds exhibited moderate to good anti-HIV-1 Integrase inhibitory activity in comparison with the reference drugs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Patil et al reported on docking and synthesis of 6-fluoro-4-quinolone-3-carboxylic acids as potential HIV-1 INIs [30,31]. The target compounds synthesized via simple twostep procedure (Scheme 13).…”
Section: Quinolines and Isoquinolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patil et al reported on docking and synthesis of 6-fluoro-4-quinolone-3-carboxylic acids as potential HIV-1 INIs [30,31]. The target compounds synthesized via simple twostep procedure (Scheme 13).…”
Section: Quinolines and Isoquinolinesmentioning
confidence: 99%
“…Hu's synthesis of pyrazolyl-4-oxo-4H-quinoline-3-carboxylic acids 54. [30,31]. The target compounds synthesized via simple two-step procedure (Scheme 13).…”
Section: Scheme 11 Original Synthesis Of Elvitegravirmentioning
confidence: 99%
“…Quinolines represent an important class of heterocycles that occur widely as natural products, pharmaceuticals, and functional materials and serve as useful synthetic building blocks in synthesis. , The construction of quinoline scaffolds is arguably one of the most important goals of the synthetic community and continues to attract the attention of synthetic chemists. Attractive methods include the catalytic annulation reactions of aromatic compounds with 2π components (e.g., alkenes and alkynes) involving C­(sp 2 )–H functionalization for targeting these skeleton constructions. , Among them, the oxidative tandem [4+2] cycloaddition of α-( N -arylamino) carbonyl compounds with alkenes has proven to be particularly efficient, which allows the formation of substituted quinolines via multiple C–H functionalization and annulation cascades (Scheme a). , However, available examples are less abundant, and a majority of them concern a limited olefin scope (e.g., monosubstituted and 1,2-disubstituted alkenes). Mancheño and co-workers first reported an FeCl 3 -promoted TEMPO oxoammonium salt-mediated dehydrogenative Povarov/oxidative tandem reaction of N -alkyl anilines with olefins for the one-pot synthesis of quinolines. , Jia, Wang, and co-workers have established a similar version for quinolines via a domino C–H functionalization/annulation of glycine derivatives with olefins using the trisarylaminium salt/InCl 3 /O 2 catalytic system. , Recently, Jia and co-workers extended the oxidative tandem annulation method to readily available 1,1-disubstituted olefins, where 3,4-dihydro-quinoline-3-ones were formed by a consecutive C–H functionalization/C–H oxidation of various glycines and N -benzylanilines.…”
mentioning
confidence: 99%